Faktor-faktor yang Mempengaruhi Status Gizi Anak 12-59 Bulan di Puskesmas Paal Merah Kota Jambi - Noval Ichsan Chasando; Abul Ainin Hapis; Cici Wuni (Universitas Ivet, 2022)
Children aged 12-59 are a period that is vulnerable to disturbances, one of which is malnutrition. Many factors can influence it, one of which is knowledge, attitude, education and parenting. This study aims to determine the relationship between mother's education level, knowledge, attitude and parenting pattern on the nutritional status of children 12-59 months. This research is a quantitative study with a cross sectional research design. The population in this study were all mothers of children under five who visited the Paal Merah Health Center in Jambi City in 2019 totaling 875 people and sampling using purposive sampling technique as many as 90 people. The analysis in this study was univariate and bivariate, with chi-square test, the research instrument used a questionnaire sheet. The results of the univariate analysis showed that there were 66 (73.3%) under-fives with good nutritional status, there were 49 (54.4%) mothers with high school education/equivalent, there were 62 (68.9%) mothers with good knowledge, there were 58 ( 64.4%) of mothers have good attitudes and there are 62 (68.9%) mothers who have good parenting patterns. The results of the bivariate analysis showed that there was a relationship between knowledge, attitudes and parenting patterns on the nutritional status of children 12-59 months and there was no relationship between education and the nutritional status of children 12-59 months at Paal Merah II Health Center Jambi City in 2021. Factors related to nutritional status is knowledge, attitudes and parenting